Fluoro‐Sorafenib (Regorafenib) effects on hepatoma cells: Growth inhibition, quiescence, and recovery12. Issue 2 (25th October 2012) - Carr, Brian I.; Cavallini, Aldo; Lippolis, Catia; D'Alessandro, Rosalba; Messa, Caterina; Refolo, Maria G.; Tafaro, Angela
Abstract: To evaluate the growth‐inhibitory properties of the potent multi‐kinase antagonist Regorafenib (Fluoro‐Sorafenib), which was synthesized as a more potent Sorafenib, a Raf inhibitor and to determine whether similar mechanisms were involved, human hepatoma cell lines were grown in the presence or absence of Regorafanib and examined for growth inhibition. Western blots were performed for Raf targets, apoptosis, and autophagy. Regorafenib inhibited growth of human Hep3B, PLC/PRF/5, and HepG2 cells in a concentration‐ and time‐dependent manner. Multiple signaling pathways were altered, including MAP kinases phospho‐ERK and phospho‐JNK and its target phospho‐c‐Jun. There was evidence for apoptosis by FACS, cleavage of caspases and increased Bax levels; as well as induction of autophagy, as judged by increased Beclin‐1 and LC3 (II) levels. Prolonged drug exposure resulted in cell quiescence. Full growth recovery occurred after drug removal, unlike with doxorubicin chemotherapy. Regorafenib is a potent inhibitor of cell growth. Cells surviving Regorafenib treatment remain viable, but quiescent and capable of regrowth following drug removal. The reversibility of tumor cell growth suppression after drug removal may have clinical implications. J. Cell. Physiol. 228: 292–297, 2013. © 2012 Wiley Periodicals, Inc.